First Identification of Naturally Infected Paratriatoma hirsuta: A Vector for Trypanosoma cruzi and Implications for Chagas Disease Transmission - Paul A. Lenhart; Walter Roachell; Robert Fathke; Bernardo Delgado; Alexander M. Potter; Ian Copeland; Francisco Sanchez; Mauricio Solis; Amanda Cline; MaeJean Ramnarace; Gena G. Lawrence; Eyal Oren; et al. (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. The first detection of Trypanosoma cruzi ( T. cruzi ) in wild-caught Paratriatoma hirsuta ( P. hirsuta ) from military installations near the United States/Mexico border in California and Arizona is reported in the present study. As part of a Chagas disease surveillance initiative, 20 adult and 63 immature P. hirsuta were collected from 16 wood rat nests, along with sympatric Triatoma rubida ( T. rubida ). Initial polymerase chain reaction (PCR) screening revealed presumptive T. cruzi -positive samples, which were reanalyzed using a novel kinetoplast PCR assay with validated targets. Amplicons were sequenced using Sanger analysis, confirming T. cruzi infection. The presence of T. cruzi was confirmed in P. hirsuta (9%) and T. rubida (7%). The present study highlights the potential role of P. hirsuta as a secondary vector in sylvatic zoonotic T. cruzi transmission cycles in the Sonoran and Mojave Deserts and how this informs Chagas disease surveillance and prevention in the region.